TET1 exerts its tumour suppressor function by regulating autophagy in glioma cells. Issue 6 (6th November 2017) - Fu, Rui; Ding, Yan; Luo, Jie; Yu, Li; Li, Cheng Lin; Li, Dong Sheng; Guo, Shi Wen
Abstract : DNA methylation and demethylation play a critical role in the regulation of the molecular pathogenesis of gliomas. Tet methylcytosine dioxygenase 1 (TET1) catalyses the sequential oxidation of 5-methylcytosine (5mC) to 5-hydroxymethylcytosine, (5hmC) leading to eventual DNA demethylation. It has been reported that TET1 is a tumour suppressor in several cancers. However, whether TET1 plays a role in glioma development is largely unclear. Different glioma specimens and corresponding normal controls were collected to analyse the expression of TET1. At the same time, TET1 of glioma U251 cells was knocked down or overexpressed to observe its effect on glioma cell proliferation and invasion as well as autophagy level. Here, we reported that the expression of TET1 in glioma tissue was significantly lower than the corresponding non-tumour normal tissues, and the concentration of TET1 is negatively correlated with the glioma WHO classification. When TET1 gene in glioma U251 cells was knocked down by CRISPR/Caspase-9 system, the proliferation and invasive ability of U251 increased remarkably. But when TET1 was overexpressed in U251 cells, the proliferation and invasion were impaired. Following the down-expression of TET1, the level of autophagy in U251 cells decreased accordingly.However, when TET1 was overexpressed in U251 cells, the level of autophagy incraesed. Furthermore, bafilomycin A1 (Baf-A1) but not 3-methyladenine (3-MA) could decrease the autophagy level of TET1 −/− U251 cells as the wild-type controls. It suggests that the tumour suppressor effect of TET1 seems to be mediated by regulating the level of autophagy, and the regulation of TET1 on autophagy is at an early stage.